Reef environments of murciélago islands and Santa Elena peninsula, Guanacaste conservation area, Costa Rican pacific - Alvarado Barrientos, Juan José (2021)
The ecology of the marine environments of the Murciélago Islands and the Santa Elena Peninsula have been studied little despite their high biodiversity. This area is influenced by a coastal upwelling. In 2014, 2016 and 2018, the region was visited to assess the composition and diversity of its reef environments. Bottom coverage, macroinvertebrate diversity and abundance, and reef fish biomass were quantified. The substrate was dominated by turf and crustose calcareous algae. Live coral coverage has decreased compared to previous reports for the area. Sea urchins were the macroinvertebrates with the highest densities, while species of commercial interest presented low densities, this may suggest some degree of fishing pressure. 84 reef fish species were identified, making the islands area with the greatest diversity of reef fish in the North Pacific of Costa Rica. Coral biotopes in this region are key to the conservation of connectivity between reef areas due to their high diversity.